Regression of Hypervascular Nodules in a Patient with Wilson's Disease Awaiting Liver Transplantation - Alcindo Pissaia; Hervé Gouya; Olivier Scatton; Filoména Conti; Yvon Calmus (Journal of Transplantation)
This paper describes the regressive course over one year of hypervascular nodules in a patient with Wilson's disease. CT revealed multiple, enhancing nodules (up to 3 cm in diameter) detected in the liver in the early arterial phase after the administration of intravenous contrast material. Most of these nodules became isodense in the portal venous phase. After one year of efficient therapy combining d-penicillamine and zinc acetate, most of the nodules had disappeared, while the liver contours had become more regular. To our knowledge, the regression of large hypervascular nodules has not previously been reported in patients with Wilson's disease.